PENGARUH LATIHAN LADDER SPEED RUN TERHADAP KECEPATAN LARI PADA TIM FUTSAL PUTRA SMP NEGERI 13 PEKANBARU - Rewa Ridozuta; Zainur Zainur; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is the lack of running speed on the men's futsal team at SMP Negeri 13 Pekanbaru, because players are slow to run to open up space forward and when they are about to counterattack the players are also very slow to run to open space to the opponent's defense area so that the opposing player has returned defensive position so the opportuAnity to score a goal has been closed. The title studied in this study is